Implementasi Bauran pemasaran “Nasi Uduk Mamah Ica” Dalam Beradaptasi Dimasa Pandemi - Azrodiana Azrodiana; Firdaus Yuni Dharta; Oky oxcygentri (Jurnal Ilmiah Wahana Pendidikan, 2022)
The pandemic has had a considerable impact on various sectors, especially for MSME players, the Central Statistics Agency (BPS) in its survey reported that only 2% of MSMEs experienced an increase in sales during the pandemic. This study aims to determine the implementation of the marketing mix applied by MSMEs of Nasi Uduk Mamah Ica as one of the MSMEs that experienced an increase in sales during the pandemic. With the hope that it can help and inspire MSMEs affected by the pandemic. This research uses a qualitative approach with primary data. The results of the study showed the implementation of the marketing mix carried out by Nasi Uduk Mamah Ica in adapting, namely 1) Products: enriching menu variations and maintaining quality. 2) Price: make 2 price variations by adjusting the market. 3) Places: less strategic but helped by the locations already available on Maps. 4) Promotion: worth of mount, e-commerce, digital marketing, and customer relationship marketing (CRM). Digital sales are the biggest change, with the wider the market, the development carried out is increasingly emerging. Digital sales are considered to be able to be a solution to adapt during a pandemic. For further research, it is necessary to look more deeply at the impact of digital sales for MSMEs during the pandemic